PERHITUNGAN POTENSI CADANGAN PANASBUMI LAPANGAN “X” MENGGUNAKAN DATA EKSPLORASI - Syahda Ahyar Habibirahman; Lestari Lestari; Bambang Kustono (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2019)
The method used in this reserve estimation is volumetric, regulated by Badan Standar Nasional Indonesia (BSNI) (SNI 13-6482-2000). This method considers that the reservoir is a form of dimensional space so that its volume can be measured. This type of method can also be used in reserve classes ranging from hypothetical resources up to proven reserves, with parameters used in this calculation obtained through assumptions and those that are the result of preliminary survey activities, which consist of geological (MT maps), geophysics (MT maps), and geochemistry (geothermometer) surveys. Data obtained from preliminary survey activities contains data on thickness, area, and temperature of the reservoir. Other parameters that have not been obtained from preliminary survey activities, such as rock porosity and heat capacity, final temperature, water and steam saturation, internal energy of water and steam, water and steam density, recovery factor, load factor and span and are based on assumptions compiled by BSNI (SNI 13-6482-2000). In addition of using volumetric methods, calculations are also performed using the Monte Carlo simulation method. This method uses random numbers as uncertainty factors in some parameters that have been obtained from the preliminary survey as mentioned above, with the type of distribution determined based on calculation parameters.. With the reservoir temperature of 220oC, area of 7.4 km2, & thickness reaches 1550 m, the potential for geothermal reserve at "X" Field based on the volumetric method is 36.90 MWe. Meanwhile, using the Monte Carlo simulation method, the potential reserves at a 90% confidence level are around 47.93 MWe: which has the the most likely reservoir temperature of 220oC with the range of values varies around 200-225oC, reservoir area with the most likely value is 7.5 km2 ranging from 4-11 km2, and the most likely thickness value is 1550 m with 1200-1700 m for the minimum and maximum values.The calculation results of the geothermal energy reserve potential in the "X" Field are 36.90 MWe using volumetric method and 47.93 for Monte Carlo simulation method.